Efektifitas alat penyaringan arang aktif batok kelapa untuk mengurangi kadar merkuri pada air Limbah Buangan Gelondong Emas di Desa Padesa Kecamatan Lantung - Lina Eta Safitri; Luh Putu Yuliastuti; Desy Fadilah Adina Putri; Fitri Setianingsih; Nurlaila Agustikawati (Jurnal Penelitian Pendidikan IPA, 2022)
The progress of the traditional gold mining industry has a positive impact on improving the quality of life of the people, but on the other hand the progress of this industry has a negative impact on the environment. Mercury contamination from traditional gold mining occurs when the processing takes place which results in the holding tank being full, so that the tailings overflow and flow into the river, especially if it rains, then mercury contamination occurs in the surrounding environment. The purpose of this study was to analyze the effectiveness of a simple filtering device for activated coconut shell charcoal to reduce mercury levels in the waste water of the logs which included optimum contact time, optimum particle size, and optimum reuse. This type of research is True Experimental Design by providing treatment (contact time, particle size and repeated use of activated charcoal). It was concluded that the absorption of mercury waste with the highest efficiency value was activated charcoal particles measuring 35 mesh (0.5 mm) with an absorption percentage of 75.81%, the highest absorption percentage of mercury waste with a contact time of 180 minutes was 88.89%, and the optimal variation of the repetition of the use of activated charcoal is 5 times.